STUDY OF THE INFLUENCE OF THE MARTIAL LAW ON TOURIST ACTIVITIES IN UKRAINE - MAMCHYN Мyroslava; DEMKO, Mariana; MYKHATS, Sofiia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The research shows that tourism in the pre-war period was an important industry for the economy of the regions of Ukraine, which generated significant economic activity and created opportunities for the employment of the population. As a result of the war, the tourist infrastructure in many regions of Ukraine was damaged, tourist companies stopped or changed their fields of activity. It was determined that the main factors influencing the development of tourism in the regions of Ukraine during the war include the availability of recreational resources, historical monuments, development of tourist infrastructure, marketing and promotion, transport accessibility, image, security of the region, political stability in the country. Since the beginning of the full-scale war, the situation in the tourist market of Ukraine has changed radically, some tourist companies have closed, others have directed their activities to volunteering. Travel companies could not resume their core activities for a long time. A certain intensification of their activities took place in the summer of 2022, but not on the entire territory of Ukraine, they researched and tested new directions. It has been established that in modern conditions, domestic tourism has its own characteristics related to specific permits and restrictions on recreation and travel introduced during the war in the relatively safe western and central regions of Ukraine, the presence of a curfew, possible shelling and the need for shelters in case of the air raids. At the same time, the demand for hotel services at the beginning of the war increased significantly in the Western regions of Ukraine. Although the war significantly affected the tourism industry, technological development and the emergence of new trends create new opportunities for the further development of the tourism industry in Ukraine today and in the post-war period. We are talking about sustainable tourism, which will allow primarily to attract environmentally conscious tourists, the introduction of digital components in tourist activities, the use of augmented reality for the promotion of tourist products. An influencer can also be used to promote a certain region and its landmarks. In the post-war period, the tourism industry should obviously develop in two directions. One direction will focus on the offer of tourist services for foreign tourists, the other - on Ukrainian tourists who will plan both foreign vacations and domestic vacations in Ukraine. Currently, the tourism industry is developing at a slow pace and must adapt to the complex current challenges.